2009
DOI: 10.1007/s10461-009-9625-z
|View full text |Cite
|
Sign up to set email alerts
|

Age and HIV Sexual Risk among Women in Methadone Treatment

Abstract: This study examines the relationship between age and HIV sexual risk behaviors among a random sample of 372 women in methadone treatment in New York City. Logistic regression results indicate that women of all ages are at risk for HIV through inconsistent condom use. Exposure to intimate partner violence (IPV), alcohol use, and HIV-negative status are associated with inconsistent condom use during vaginal sex. Age (35-44), having a main sexual partner with an HIV risk factor, IPV, and alcohol use are associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 82 publications
2
15
0
Order By: Relevance
“…While findings are consistent with recent studies suggesting that midlife/older women remain sexually active and are just as likely as their younger counterparts to engage in high-risk sexual behaviors (Engstrom, et al, 2011; Kwiatkowski & Booth, 2003; Theall, Elifson, Sterk, & Klein, 2003; Zablotsky & Kennedy, 2003), our research further highlights how midlife/older women’s HIV risk is shaped by low levels of HIV prevention knowledge and condom use self-efficacy and exacerbated by experiences of MA use and PV. Quantitative findings indicate 75–80% of midlife/older women reported being high on MA during unprotected sex with various partner types, while our qualitative sample attributed their inability to engage in safer sex to being under the influence of drugs, having sexual partners who refused condom use, avoiding violence perpetrated by male partners, age-related physiological characteristics (e.g., impotence, vaginal dryness) and feeling they had “aged out” of HIV risks.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While findings are consistent with recent studies suggesting that midlife/older women remain sexually active and are just as likely as their younger counterparts to engage in high-risk sexual behaviors (Engstrom, et al, 2011; Kwiatkowski & Booth, 2003; Theall, Elifson, Sterk, & Klein, 2003; Zablotsky & Kennedy, 2003), our research further highlights how midlife/older women’s HIV risk is shaped by low levels of HIV prevention knowledge and condom use self-efficacy and exacerbated by experiences of MA use and PV. Quantitative findings indicate 75–80% of midlife/older women reported being high on MA during unprotected sex with various partner types, while our qualitative sample attributed their inability to engage in safer sex to being under the influence of drugs, having sexual partners who refused condom use, avoiding violence perpetrated by male partners, age-related physiological characteristics (e.g., impotence, vaginal dryness) and feeling they had “aged out” of HIV risks.…”
Section: Discussionsupporting
confidence: 90%
“…Midlife/older women engage in sexual activities well into their 70’s and 80’s, but may not utilize prevention methods due to declining fertility or impotence experienced by an intimate partner (Lindau et al, 2007; Sherman, Harvey, & Noell, 2005; Zablotsky & Kennedy, 2003). Research has shown that sexual risk behaviors (e.g., sex while under the influence of alcohol and/or drugs, unprotected sex) for midlife/older women are similar to those of younger aged women (Minkin, 2010; Engstrom, Shibusawa, El-Bassel, & Gilbert, 2011). Although sexual risk behaviors are similar for both groups, the rationale for engaging in these behaviors is different (e.g., midlife/older women less likely to reproduce, physiologically difficult for older men to use condoms).…”
Section: Introductionmentioning
confidence: 99%
“…These findings may reflect factors contributing to differences by gender, such as the role of intimate partner violence, sexual risk reduction self-efficacy and partner-level factors (Somlai et al, 2003; Kapadia et al, 2007; Engstrom et al, 2011; Kapadia et al, 2011). Recent heroin and alcohol use were also associated with non-condom use in our study, which is consistent with existing literature (Metzger et al, 1993; Kalichman et al, 2002; Des Jarlais et al, 2007; Theall et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…Extant literature documents elevated HIV/STI transmission among substance abusers (Kral et al, 2001; Strathdee et al, 2001), which result from unsafe injection practices, impaired use of preventative “safe sex” strategies, and the interplay of sociocultural influences (e.g., commercial sex, criminality). Both male and female treatment seekers exhibit high rates of risky sexual acts, including those undertaken with new partners, during intoxicated states, and without condoms (Engstrom, Shibusawa, El-Bassel, & Gilbert, 2011; Rondinelli et al, 2009). Enrollment in addiction treatment may prompt cessation of drug use that reduces sexual risk, but the resulting sexual abstinence is often only a short-term solution.…”
Section: Introductionmentioning
confidence: 99%